Tripling Optical Efficiency of Pancake Optics for Virtual Reality Displays - Yuze Xiao; Jiazhan Zhang; Yun Ye; Sheng Xu; Qun Yan; Tailiang Guo; Enguo Chen (Crystals)
The pancake structure is the mainstream optical solution for virtual reality (VR) displays due to its compact, folded optical path. However, only a small portion of the light can pass through the pancake optical engine because the incident light has to be polarized and directed to the half mirror (HM) twice. In order to improve the optical efficiency, a new pancake optical engine is proposed for VR display, which employs a diffractive deflection film (DDF) with different focal lengths in three regions and two cholesteric liquid crystal (CLC) lenses that respond to circularly polarized light. The CLC lenses are modeled, and their polarization response characteristics are verified. The pancake system is simulated and optimized in terms of image quality and evaluated for optical efficiency, achieving 2.86 times the optical efficiency of the conventional pancake system, and the root mean square (RMS) radius of the system is controlled within 19 μm, and the modulation transfer function (MTF) at the cut-off frequency is greater than 0.2. The results indicate that this structure has great potential in the VR display field.